Pengaruh Indeks Massa Tubuh terhadap Klasifikasi Tekanan Darah pada Penduduk Usia Produktif di Kota Medan - Darren Gosal; Yohanes Firmansyah; Ernawati Su (Fakultas Kedokteran Universitas Kristen Krida Wacana, 2020)
Hypertension is a chronic condition characterized by elevated blood pressure, with systolic pressure of more than 140 mmHg and/or diastolic pressure of more than 90 mmHg. Hypertension is a global problem, which has affected 1.13 billion people worldwide. Increase of body mass index (BMI) is associated with hypertension incidence. The purpose of this study was to find out the effect of body mass index to hypertension incidence and blood pressure classification at productive age citizen in Medan. This study used a cross sectional type approach with questionnaire, blood pressure measurement, body weight, and body height measurement. A total of 352 respondents participated in this study, all were workers who came to the workplace clinic. Anova test analysis was used, followed by a Post Hoc Bonferroni. Results showed that there was an effect of BMI to hypertension incidence (p-value< 0,001). The study observed a significant difference in BMI between respondents with hypertension grade 1 and grade 2 groups (p-value< 0,001). The study concludes that BMI affects hypertension incidence and there is significant difference of BMI between grade 1 hypertension and grade 2 hypertension (p-value< 0,001).